EXPLORING THE RELATIONSHIP BETWEEN BODY TEMPERAMENTS AND ANTHROPOMETRIC INDICES AS PREDICTORS OF DISEASE RISK AMONG UNDERGRADUATE STUDENTS (The Research of Medical Science Review, 2025)
This study explores the relationship between Traditional body temperaments and anthropometric indices, including Body Mass Index (BMI), Waist/Hip Ratio (WHR), and Relative Fat Mass (RFM), to predict disease risks among undergraduate medical students. Traditional medicine classifies individuals into four temperaments (Sanguine, Choleric, Melancholic, Phlegmatic), each linked to distinct health profiles. Anthropometric data from 116 students were analyzed using ANOVA and post-hoc tests to determine significant differences in BMI, WHR, and RFM across temperaments. The results indicated that Phlegmatic individuals have the highest BMI and WHR, correlating with higher risks for cardiovascular diseases and diabetes. The findings underscore the value of integrating traditional temperament assessments with modern health metrics to guide personalized healthcare strategies.